Physiotherapeutic approach to Attention Deficit Hyperactivity Disorder (ADHD) (Research, Society and Development, 2022)
Physiotherapy is one of the areas that can act in the process of diagnosis and monitoring of Attention Deficit/Hyperactivity Disorder (ADHD). In this sense, the objective was to outline the studies and development of technologies on the subject and the physiotherapeutic approaches already registered in databases. The search was conducted from January to July 2022, the descriptors used were "ADHD AND Physiotherapy" being performed on the World Intellectual Property Organization (WIPO) patent database and articles and abstracts: Scopus Web of Science, PubMed, The Lens and ScienceDirect. Using the Scopus Web of Science, PubMed, The Lens and ScienceDirect article bases and the descriptors “ADHD AND Physiotherapy”. It is concluded that the role of physiotherapy in the development and monitoring of people with ADHD, from diagnosis, with exercises and activities that help in motor, neurological and cognitive progression, becomes relevant for promoting health and quality of life for these patients.